The Impact of Village Government Size, Wealth, and Intergovernmental Revenue on Village Financial Performance in Krian District, Sidoarjo, East Java - Imamah, Nurul; Iradawaty, Sofiah Nur; Rahman, Arief; Fauziah, Dien Ajeng; Siswati, Endang (Dinasti Publisher, 2025)
This study aims to analyze the impact of village government size, wealth, and intergovernmental revenue on village financial performance. The research method used is descriptive quantitative. The population in this study included all villages in the Krian sub-district, and sampling was determined by purposive sampling method with a total observation sample of 30 villages. The data analysis method uses Multiple Linear Regression techniques. The study found that village financial performance is positively and significantly influenced by size and wealth, but not by intergovernmental revenue. However, when considering all three factors together, size, wealth, and intergovernmental revenue have a significant impact on village financial performance. Village government financial performance refers to the ability of the village to explore, manage, and utilize its financial resources to support the government system, community services, and village development, without full dependence on the central government. The implications of this research are to support the performance of a healthy village government. The originality of this research is in health and intergovenmental revenue.